Inverse Hall-Petch Nature of Fe-Ni-Cr-Co-Cu High Entropy Alloy at Atomic Scale - Zaenudin, Mohamad; Gamayel, Adhes; Saleh, Yasya Khalif Perdana; Abdulrazzaq, Mohammed N (International Journal of Integrated Engineering, 2024)
High entropy alloy is a class material composed of several principal elements with equiatomic composition. The entropic of this material with near equiatomic configuration composition can theoretically decrease the strength-ductility trade-off, which differs their application from their classical alloy counterpart. The strength of nanocrystalline materials, known as the Hall-Petch phenomenon, tends to increase. Still, when it hits the critical grain size, the softening behavior of decreasing strength is observed and known as the inverse Hall-Petch phenomenon. Although there are numerous reports on the inverse Hall-Petch effect, both numerically and experimentally, the deformation mechanism of these materials is not clearly described, especially at the atomic scale. This study aims to tackle the issue by reporting the molecular dynamics simulation of nanocrystalline Fe-Ni-Cr-Co-Cu high entropy alloy with an average grain size of 7.3 nm3, 6.8 nm3, and 6.4 nm3. The study shows that the tensile deformation is mainly attributed to the grain boundary sliding due to the high grain boundary volume within the system. However, in the case of compressive deformation, at the earlier stage, the deformation is mainly focused on the grain boundary deformation, although the new cluster of grain has infrequently happened due to the compression. Both tensile and compressive strength exbibit the inverse Hall-Petch nature of Fe-Ni-Cr-Co-Cu high entropy alloy.